Expression of Otx Genes in Müller Cells Using an In Vitro Experimental Model of Retinal Hypoxia. (31st December 2021) - Azzolini, Claudio; Donati, Simone; Micheloni, Giovanni; Moretti, Vittoria; Valli, Roberto; Acquati, Francesco; Costantino, Lucy; Ferrara, Fulvio; Borroni, Davide; Premi, Elias; Testa, Francesco; Simonelli, Francesca; et al.
Abstract : Introduction . Müller glial cells typically activate to react to hypoxic tissue damage in several retinal diseases. We evaluated the in vitro response to a hypoxia-mimicking stimulus on the expression of a set of genes, known to contribute to eye morphogenesis and cell differentiation. Materials and Methods . A MIO-M1 Müller cell line was cultured in a hypoxia-mimicking environment by the addition of cobalt chloride to the culture medium, followed by a recovery time in which we mimic restoration from the hypoxic insult. The HIF-1 α protein and VEGF-A gene expression were quantified to verify the induction of a hypoxia-like state. Results . Among the genes under study, we did not observe any difference in the expression levels of Otx1 and Otx2 during treatment; conversely, Otx1 was overexpressed during recovery steps. The VEGF-A gene was strongly upregulated at both the CoCl2 and recovery time points. The transactivated isoform (TA) of the TP73 gene showed an overexpression in long-term exposure to the hypoxic stimulus with a further increase after recovery. Discussion . Our molecular analysis is able to describe the activation of a set of genes, never before described, that can drive the response to a hypoxia-like status. The improved comprehension of these cellular events will be useful for designing new therapeutical approaches for retinal pathologies.